Dampak Pemilihan Waktu dan Cara Melahirkan pada Wanita dengan Riwayat Seksio Sesarea terhadap Luaran Ibu dan Neonatal: Suatu Systematic Review - Pinda Hutajulu; Nur Maharani Balqis (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
The increasing number of cesarean sections (SC) globally has an impact on the increasing number of pregnant women with a history of previous surgeries. The choice between trial of labor after cesarean (TOLAC) and elective repeat cesarean section (ERCS) is a clinical challenge in balancing maternal and infant safety. This systematic review follows the guidelines of PRISMA 2020, with literature searches in PubMed, Scopus, Cochrane Library, and Google Scholar (2015–2025). The studies analyzed included cohort design, prospective, retrospective, meta-analysis, and cross-section evaluating women with a single history of SC, single pregnancy, and head presentation. A total of 20 studies with a total of 1,096,999 participants were identified. The success of TOLAC is reported to reach 60–85% in developed countries and 30–40% in developing countries. The risk of uterine rupture was higher in TOLAC (1.3%; OR 2.01–3.35) compared to ERCS (~0%), but in absolute terms remains low. TOLAC that failed to improve maternal and neonatal morbidity, while ERCS before 39 weeks was associated with respiratory distress and early neonatal death. The implementation of ERCS ≥39 weeks reduced complications without increasing maternal risk. Both methods are relatively safe if performed in adequate facilities, and clinical decisions should be tailored to gestational age, mother-fetal condition, and readiness of obstetric emergency services.